Demonstration of increased corrosion activity for insulated pipe systems using a simplified electrochemical potential noise method. (May 2017) - Caines, Susan; Khan, Faisal; Shirokoff, John; Qiu, Wei
Abstract: Corrosion under insulation (CUI) is a significant issue in industry. When a component is insulated, moisture could become trapped at pipe surfaces and lead to corrosion. The severity of corrosion under insulation could be considered greater than a component without insulation in a similar environment. This belief has not yet been demonstrated or reported in the literature. To understand CUI, the difference in a system under insulation and a system without insulation must be determined to confirm the anecdotally held understanding that corrosion can be more severe under insulation. Experiments were conducted to demonstrate this difference in corrosion severity of pipe surfaces exposed to insulation and surfaces without insulation. Increased mass loss and corrosion rates were found for electrodes under insulation over electrodes without insulation. The increase in corrosion was found using a simplified electrochemical potential noise (EPN) method and confirmed through visual observation and mass loss data. Highlights: A new electrochemical noise method for corrosion monitoring. Testing and validation of the new method. Application of the electrochemical noise method on corrosion under insulation monitoring.